The Role Of Personal Branding In Mediating Digital Literacy, Entrepreneurial Orientation, And Community Support For Entrepreneurial Marketing Among Gig Workers In Bali - I Gusti Ayu Dinda Kusuma Dewi; Putu Dyah Permatha Korry (Journal of Management, Economic, and Accounting, 2026)
The development of digital technology has transformed traditional work patterns into more flexible ones through the emergence of the gig economy, where individuals work independently on a project-based basis with the support of digital platforms. This study aims to analyze the influence of digital literacy, entrepreneurial orientation, and community support on entrepreneurial marketing, with personal branding as a mediating variable among gig workers in Bali. This research approach is quantitative, with a conceptual population consisting of all gig workers in Bali who work based on digital platforms. The sampling technique used non-probability purposive sampling. Data analysis was conducted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results are expected to show that digital literacy, entrepreneurial orientation, and community support have a positive effect on personal branding and entrepreneurial marketing, both directly and indirectly. Personal branding is predicted to play a significant mediating role in strengthening the relationship between these variables and entrepreneurial marketing. This study provides a theoretical contribution in broadening the understanding of entrepreneurship-based marketing strategies in the digital era and provides practical implications for gig workers in Bali to build a professional image, expand networks, and increase competitiveness through strengthening digital literacy and work communities.